Implementation of Integrated Curriculum in Improving Islamic Religious Education Learning Outcomes at Peacesantren Welas Asih Junior High School In Garut - Sri Utari; Nenden Munawaroh; Iman Saifullah; Ijudin; Masripah (al-Afkar, Journal For Islamic Studies, 2025)
The integrated curriculum is an interdisciplinary approach, combining various disciplines into one learning experience to create a holistic education. This curriculum has been applied since the establishment of the Islamic Boarding School to improve the quality of education to remain relevant to the needs of the community. This study uses qualitative research methods which include data collection through observation, interviews, and documentation. This study aims to determine the integrated curriculum system of Welas Asih Islamic Boarding School, how the application of curriculum integration in improving PAI learning outcomes at Welas Asih Islamic Boarding School and to find out the supporting and inhibiting factors in improving learning outcomes at Welas Asih Islamic Boarding School. The results of this study show that Welas Asih Islamic Boarding School integrates the curriculum by making a separate module book that contains various disciplines. The implementation of an integrated curriculum has a positive impact on improving the knowledge and skills of students. Supporting factors for the implementation of this curriculum include the competence of teachers who have met academic qualifications, training every three months to improve the competence of teachers and the involvement of parents through the ABWA community (father mother Welas Asih) which supports the learning process. However, obstacles such as the difficulty of some students in socializing and inadequate facilities such as a mosque that can accommodate all students.